Enhancing Industrial Communication with Ethernet/Internet Protocol: A Study and Analysis of Real-Time Cooperative Robot Communication and Automation via Transmission Control Protocol/Internet Protocol - Seong, JuYong; Ranjan, Rahul; Kye, Joongeup; Lee, Seungjae; Lee, Sungchul (Sensors (Basel, Switzerland), 2023)
This study explores the important task of validating data exchange between a control box, a Programmable Logic Controller (PLC), and a robot in an industrial setting. To achieve this, we adopt a unique approach utilizing both a virtual PLC simulator and an actual PLC device. We introduce an innovative industrial communication module to facilitate the efficient collection and storage of data among these interconnected entities. The main aim of this inquiry is to examine the implementation of Ethernet/IP (EIP), a relatively new addition to the industrial network scenery. It was designed using ODVA’s Common Industrial Protocol (CIP™). The Costumed real-time data communication module was programmed in C++ for the Linux Debian platform and elegantly demonstrates the impressive versatility of EIP as a means for effective data transfer in an industrial environment. The study’s findings provide valuable insights into Ethernet/IP’s functionalities and capabilities in industrial networks, bringing attention to its possible applications in industrial robotics. By connecting theoretical knowledge and practical implementation, this research makes a significant contribution to the continued development of industrial communication systems, ultimately improving the efficiency and effectiveness of automation processes.